2004
DOI: 10.1196/annals.1331.043
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Changes in α‐ and γ‐Tocopherol Levels during Coronary Artery Bypass Grafting

Abstract: We studied whether cardiopulmonary bypass (CPB) has any immediate impact on the initiation of antioxidative defenses in the body by measuring F(2)-isoprostanes and alpha- and gamma-tocopherol, respectively. 8-iso-PGF(2alpha) levels increased significantly within 3 minutes and until the end of CPB. alpha-Tocopherol levels increased gradually at 20 min during CPB and continued until 6 hours after CPB. gamma-Tocopherol levels followed a similar fashion at the end of CPB. 8-iso-PGF(2alpha) and tocopherol levels ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Oxidative stress has been demonstrated to be increased during CPB. [ 26 ] The brain is especially susceptible to oxidative stress due to abundant lipid content in myelin sheaths, and antioxidant level has been demonstrated to be related to postoperative delirium in patients undergoing CPB surgery. [ 27 ] Cerebral damage induced by oxidative stress during DHCA attracts lots of attention, and excitatory amino acids were observed to increase significantly after DHCA.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been demonstrated to be increased during CPB. [ 26 ] The brain is especially susceptible to oxidative stress due to abundant lipid content in myelin sheaths, and antioxidant level has been demonstrated to be related to postoperative delirium in patients undergoing CPB surgery. [ 27 ] Cerebral damage induced by oxidative stress during DHCA attracts lots of attention, and excitatory amino acids were observed to increase significantly after DHCA.…”
Section: Discussionmentioning
confidence: 99%
“…5 The intraoperative increase in plasma F2-isoprostanes reported by Lopez et al is consistent with previous findings. 6 Importantly, these previous studies also reported a concomitant gradual intraoperative increase in circulating antioxidants αand γ-tocopherol. This suggests that an adaptive upregulation of antioxidant counterregulatory response to the oxidative injury associated with CPB is at play.…”
mentioning
confidence: 86%